Measurement and analysis on the teeth morphology in 90 Chinese Han young adults with normal occlusion - Chen, Li; Pan, Jie; Zhou, Feng-Cheng; Liu, Yue-Hua (Shanghai kou qiang yi xue, 2018)
To measure and analyze the teeth surfaces in 90 Chinese Han young adults with normal occlusion from one university in Shanghai, and to provide data for straight wire appliance system for Chinese patients. 90 volunteers with normal occlusion were selected from 9000 college freshmen in Shanghai，whose dental impression with normal occlusion were scanned into digital models. Crown angulation, crown inclination, buccal(labial) crown facial prominence were measured and analyzed by Smartee Ortho（A）software. SPSS 17.0 software package was used for statistical analysis. The mean values of the teeth surfaces in normal occlusion were obtained, including crown angulation, crown inclination, buccal (labial) crown facial prominence. Crown angulations were leaning toward the middle line except upper second molars. Compared with west Caucasian, angulations were smaller in incisors and canines, and crown inclinations were larger in incisors and canines, especially the upper and lower canines. The upper and lower molars were i